1995
DOI: 10.1007/bf00346224
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma complicating perianal hidradenitis suppurativa

Abstract: Hidradenitis suppurativa or Verneuil's disease is usually a chronic, recurrent, suppurative and cicatricial disorder. It most often affects the skin of the axillae, groins and perineum, and less commonly the buttocks and upper thighs. A squamous cell carcinoma located in the hidradenitis-affected area is a rare complication. We present a review of the twenty-six published cases adding one of our own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 17 publications
0
19
0
8
Order By: Relevance
“…Hidradenitis suppurativa is a recurrent chronic inflammatory disease of the apocrine glands that most commonly involves the axillary, perianal, perineal, and inframammary regions [168][169][170][171] and less commonly the buttocks and upper thighs [168].…”
Section: Hidradenitis Suppurativa (Hs) and Cancer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hidradenitis suppurativa is a recurrent chronic inflammatory disease of the apocrine glands that most commonly involves the axillary, perianal, perineal, and inframammary regions [168][169][170][171] and less commonly the buttocks and upper thighs [168].…”
Section: Hidradenitis Suppurativa (Hs) and Cancer Developmentmentioning
confidence: 99%
“…The etiology of this suppurative and cicatricial disorder [168] is poorly understood; however, a genetic component, hormonal influence, and obesity are linked to its expression [172]. Characteristic histopathological findings include dilated keratinfilled pores, abscesses, scarring, sinus tract formation, malodorous discharge and inflammation with secondary infection [170].…”
Section: Hidradenitis Suppurativa (Hs) and Cancer Developmentmentioning
confidence: 99%
“…The chronic inflammation associated with the disease annoys patients because of its physical and psychological burden 11,12 . Studies have reported malignant tumours such as squamous cell carcinoma arising in chronic gluteal hidradenitis suppurativa [13][14][15][16] . Thus, the treatment strategy should be chosen according to the disease presentation 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Cette lésion peut être unique ou multiple, confluant alors en placard bosselé. Elle peut régresser spontanément, mais le plus souvent elle va se fistuliser à la peau laissant s'écouler un liquide séropurulent [1,3].…”
Section: Discussionunclassified
“…Elle est le plus souvent associée à d'autres localisations. Le siège inguinoscrotal et pubien est retrouvé dans 90 % des cas [1], la région axillaire dans 26 % des cas [2], la nuque dans 16 % des cas, la région rétroauriculaire dans 6 % des cas [2], enfin le mamelon dans 4 % des cas [3], ce qui conforte l'intérêt d'un examen clinique soigneux.…”
Section: Discussionunclassified